Language of things - Sudjic, Deyan (New York : Penguin Books, 2009)
Sudjic charts our relationship--both innocent and knowing--with all things designed. From the opulent excesses of the catwalk to the playfulness of an Alessi jam jar, he shows how we can be manipulated and seduced by our possessions. With scintillating wit he addresses these questions and more, exploring the reasons why every designer yearns to put a personal stamp on a chair or an adjustable lamp, and where design ends and art begins.--From publisher description.
"First published in Great Britain in 2008 by Allen Lane"--T.p. verso.
Includes bibliographical references (p. [197]-198) and index.
Keywords: Design -- Philosophy; Design -- Social aspects